Efficient Use of Satellite Gravity Anomalies for mapping the Great Sumatran Fault in Aceh Province - Muhammad Yanis; Marwan Marwan; Nazli Ismail (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2019)
Gravity Satellite has been widely used in tectonic studies and regional of geological mapping. The Satellite Gravity data are provided free by Scripps Institution of Oceanography, University of California San Diego. The data are acquired by GEOSAT and ERS-1 satellites with a 1.5 km resolution for one pixel. For a further application, the tilt derivative analytic technique was used in order to enhance linear trends of the geological structure revealed by the Bouguer anomalies. The method is represented by the value of an angle between the total horizontal and vertical derivative from the gravity data. The results show that the tilt derivative calculation has been able to map clearly some geological structures on the north of Sumatra i.e., the Aceh and the Seulimeuem segments, as well as some local faults around them. On the other hand, Banda Aceh as the capital city of Aceh Province and Pidie District is dominated by positive values of the tilt derivative anomalies. The data coincide with geological maps of both areas where they are covered by alluvial deposits. Based on the result, it can be concluded that the tilt derivative method is potentially used for quick interpretation of the satellite gravity data.